Weaving Cultural Relevance and Achievement Motivation Into Inclusive Classroom Cultures. Issue 2 (3rd April 2018) - Kumar, Revathy; Zusho, Akane; Bondie, Rhonda
Abstract : Despite shifting demographic trends, research on motivation generally remains focused on European American, middle-class, educated samples, calling into question its utility and overall generalizability. Thus, the overarching purpose of this article is to increase the practical and cultural relevance of motivational research. Specifically, we review four key principles of motivation—meaningfulness, competence, autonomy, and relatedness—and unpack how they align with the research on culturally responsive and relevant education. Ultimately our goal is to emphasize the importance of interdisciplinary research and to demonstrate how the principles of culturally responsive education are instantiated in motivationally supportive classrooms where teachers are more culturally sensitive and create an environment where cultural differences are appreciated and valued.